SOIL FERTILITY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The soil-climatic conditions of the country create favorable conditions for obtaining grain and nutritious food for livestock twice a year from irrigated lands, sowing of secondary crops after winter wheat creates favorable conditions for improving soil fertility. Especially from legumes, mash, beans and soybeans not only increases soil fertility, but is also a nutritious fodder for livestock. In other words, in the experiment, it was revealed that in mash grain there is (15,2 c/ha) 1991.1 kg/ha, in mash hay – (32.2 c/ha) 1032.3 kg/ha, a total of 3023.4 kg/ha of the nutrient unit, and it was also determined  443.8 kg/ha and 89.8 kg/ha of protein, respectively, and a total of 533.6 kg/ha of protein.